Urban green area provides refuge for native small mammal biodiversity in a rapidly expanding city in Ghana - Ofori, Benjamin Y.; Garshong, Reuben A.; Gbogbo, Francis; Owusu, Erasmus H.; Attuquayefio, Daniel K. (Environmental Monitoring and Assessment, 2018)
Urbanization is a key driver of global biodiversity loss. Although sub-Saharan African countries are experiencing unprecedented urbanization and urban expansion, very little is known about how this impacts tropical biodiversity. Here, we assessed the effects of urban expansion and urban green space on local small mammal species diversity in Accra, Ghana. We surveyed small mammals in the University of Ghana botanical garden, an urban green area (UGA) and adjoining built-up environment (BE) and compared the results with baseline data (BLD) collected when large areas of the current city still remained mostly undeveloped. The methodology involved live-trapping using Sherman collapsible live-traps. Our data showed higher small mammal abundance and diversity in the UGA than BE. Similarity of species composition was higher between UGA and BLD than between BE and BLD. The small mammal species captured in BE (the rodents Mastomys erythroleucus , Rattus rattus , and Arvicanthis rufinus , and the shrew Crocidura olivieri ) are known to easily adapt to human-modified landscapes. Our results suggest that urbanization negatively influenced the abundance, diversity, and community composition of small mammals. Efforts should be directed towards the integration of urban green areas into urban land development planning in developing countries in order to conserve local wildlife and ecological services that enhance the quality of urban life.